The Impact of the First Wave of the COVID-19 Pandemic on Trade between Canada and the United States - Miguel Cardoso; Brandon Malloy (ZBW - Leibniz Information Centre for Economics, 2021)
We examine how the COVID-19 pandemic has impacted trade between Canada and the U.S., using a novel dataset on monthly bilateral trade flows between Canadian provinces and U.S. states, merged with COVID-19 health data. We find a statistically significant and robust negative relationship between the severity of COVID-19 and changes in Canadian exports and imports. Our results show that a one-standard deviation rise in COVID-19 severity in a Canadian province leads to a fall of 3.1-4.9% in exports and a 6.7-9.1% fall in imports. This result is robust to the measure of COVID-19 severity used: case levels, hospitalizations or deaths. We also investigate the role of COVID-19 policy responses and find that lockdown stringency measures did not significantly affect Canadian export or import flows. Decomposing our analysis by industry, we determine that trade in the relatively more labour-intensive manufacturing industry was most negatively affected by the pandemic, while the agriculture industry suffered the least disruption to trade flows. Collectively our results suggest that while trade was most adversely affected in industries and regions hardest hit by the pandemic, government-imposed lockdown restrictions do not appear to have caused significant additional decreases in Canadian exports or imports.
Keywords: F15; F53; 330; COVID-19; international trade; lockdown restrictions; manufacturing